Analysis of the ΣPhi/Ph/1 Queue - Bitran, Gabriel R.; Dasu, Sriram (Operations research, 1994)
In this paper, we analyze a queue to which the arrival process is the superposition of separate arrival streams, each of whose interarrival time distributions is of phase type, and the service time distribution is also of phase type. The performance measures derived for this queue include: the distribution of the number in the system as seen by each customer class upon arrival, Laplace-Stieltjes transform (LST) of the waiting-time distribution for each customer class, stationary interdeparture time distribution and the lag correlation coefficients of the departure process, and characteristics of the tails of the waiting time and queue length distributions.